Flood adaptive settlements towards urban development in the Riparian of Meureudu River, Aceh Province, Indonesia / Mirza Irwansyah, Cut Nursaniah and Laila Qadri - Irwansyah, Mirza; Nursaniah, Cut; Qadri, Laila (Universiti Teknologi MARA, Perak, 2019)
Meureudu Riparian in the past was a place of a collective settlements;it was then developed to become a Meureudu City in Aceh Province, Indonesia. Initially, it was formed as traditional fishermen settlements but now has shifted into semi-modern settlements. However, the settlements developed sporadically to form an unplanned pattern of settlements. This condition resulted in low maintaining river and non-adaptive existence of the dwellings with the environment. Floods occur repeatedly in the river that affected great lost to the community. This study aimed to propose residential pattern design and adaptive settlements with Meureudu River riparian. Easy access roads to markets will facilitate economy growth to the people.This will also cause large numbers of unbridled migrants to enter and build settlements. In this study the a combination of quantitative methods based on interview data and questionnaires and qualitative exploratory methods based on field observation were used. The data were collected through observation, field measurement and secondary data sources. The results show that the condition of settlements along the river basin do not reflect the culture of the river. In order not to further aggravate the condition of the settlement and its impact on the occupants, we recommended two types of houses, namely in the form of stage and non-stage. The stage houses are located on the riverfront with an orientation overlooking the river. Additionally, undersea area can be used as security from the puddle of river water runoff during the flood and as a garden area and public while dry, while at a distance of 100 meters from the river non-stage houses form would be built because the runoff of flood water no longer affects the occupancy.